Perancangan Aplikasi Game Berbasis Virtual Reality Dengan Tema Sejarah - Fairuz Wiwanata, Ika Puspa; Nugraha, Bagas Satya Dian; Pradibta, Hendra (MULTINETICS, 2021)
At this time, learning history is not widely favored due to its boring learning media. Because of that, a more engaging and interactive learning media is needed. Accordingly, a Virtual Reality-based game learning media was made with the theme being Attack of the Dead Men which occurred during World War I. This game was built using Unity application version 2019.3.1f1 Personal with the coding language C++ in which written using Visual Studio 2019 application. The needed assets were taken from various sources either free or paid. Method used in this development was the Multimedia Development Life Cycle method or MDLC. The result of this planning and building was a Virtual Realitybased game with a history theme. The game was then tested directly using the VR tool on 8 respondents from various backgrounds with the age range of 13-60, both with or without experience using a VR tool prior. The results gathered from questionnaires distributed to respondents after the test were 50% respondents stated that the information provided was easy to digest and 62.5% respondents considered the gameplay was quite engaging enough.